Mononuclear Cell Recruitment, Granuloma Assembly, and Response to Treatment in Experimental Visceral Leishmaniasis: Intracellular Adhesion Molecule 1-Dependent and -Independent Regulation - Murray, Henry W. (American Society for Microbiology, 2000)
In experimental visceral leishmaniasis, acquired resistance to intracellular Leishmania donovani is Th1 cell cytokine dependent and largely mediated by gamma interferon (IFN-γ); the same response also permits conventional antimony (Sb) chemotherapy to express its leishmanicidal effect. Since the influxing blood monocyte (which utilizes endothelial cell ICAM-1 for adhesion and tissue entry) is a primary effector target cell for this cytokine mechanism, we tested the monocyte's role in host responsiveness to chemotherapy in mice with ICAM-1 gene disruptions. Mutant animals failed to develop any early granulomatous tissue response in the liver, initially supported high-level visceral parasite replication, and showed no killing after Sb treatment; the leishmanicidal response to a directly acting, alternative chemotherapeutic probe, amphotericin B, was intact. However, mutant mice proceeded to express a compensatory, ICAM-1-independent response leading to mononuclear cell influx and granuloma assembly, control over visceral infection, and the capacity to respond to Sb. Together, these results point to the recruitment of emigrant monocytes and mononuclear cell granuloma formation, mediated by ICAM-1-dependent and -independent pathways, as critical determinants of host responsiveness to conventional antileishmanial chemotherapy.